IMPLEMENTATION OF PRINCIPLES OF INTERDISCIPLINARY LINKS IN PROFESSIONAL TRAINING IN EU COUNTRIES - Svitlana Zaskaleta (Borys Grinchenko Kyiv Metropolitan University, 2019)
The article deals with the conceptual foundations and the search for effective ways of developing the system of higher education in Ukraine. It has been determined that the general tendency of professional training of specialists in the countries of the European Union is the applied interdisciplinary approach. An interdisciplinary approach is analyzed in the process of studying humanitarian disciplines. The quality of professional training depends on the relationship between teaching disciplines, as well as the ability of the teacher to call and support the subjects of learning interest in such relationships. The concept of «integration» is specified, the meaning of «interdisciplinary connections» is substantiated. The strategic directions of updating the learning process based on the application of the principles of interdisciplinary connections in the process of studying a foreign language are determined